Broad habitat range of the phylogenetically narrow R-BT065 cluster, representing a core group of the Betaproteobacterial genus Limnohabitans - Simek, Karel; Kasalicky, Vojtech; Jezbera, Jan; Jezberová, Jitka; Hejzlar, Josef; Hahn, Martin W (Applied and environmental microbiology, 2010)
The distribution of the phylogenetically narrow R-BT065 cluster (Betaproteobacteria) in 102 freshwater lakes, reservoirs, and various ponds located in central Europe (a total of 122 samples) was examined by using a cluster-specific fluorescence in situ hybridization probe. These habitats differ markedly in pH, conductivity, trophic status, surface area, altitude, bedrock type, and other limnological characteristics. Despite the broad ecological diversity of the habitats investigated, the cluster was detected in 96.7% of the systems, and its occurrence was not restricted to a certain habitat type. However, the relative proportions of the cluster in the total bacterioplankton were significantly lower in humic and acidified lakes than in pH-neutral or alkaline habitats. On average, the cluster accounted for 9.4% of the total bacterioplankton (range, 0 to 29%). The relative abundance and absolute abundance of these bacteria were significantly and positively related to higher pH, conductivity, and the proportion of low-molecular-weight compounds in dissolved organic carbon (DOC) and negatively related to the total DOC and dissolved aromatic carbon contents. Together, these parameters explained 55.3% of the variability in the occurrence of the cluster. Surprisingly, no clear relationship of the R-BT065 bacteria to factors indicating the trophic status of habitats (i.e., different forms of phosphorus and chlorophyll a content) was found. Based on our results and previously published data, we concluded that the R-BT065 cluster represents a ubiquitous, highly active segment of bacterioplankton in nonacidic lakes and ponds and that alga-derived substrates likely form the main pool of substrates responsible for its high growth potential and broad distribution in freshwater habitats.
Keywords: nadmořská výška; Cluster Analysis; Colony Count, Microbial; genetická variace; hybridizace in situ fluorescenční; fosfor; chlorofyl a; fylogeneze; Ecosystem; Betaproteobacteria; RNA, Ribosomal, 16S; RNA, Ribosomal, 18S; Sequence Analysis, DNA; Phylogeny; uhlík; Chlorophyll; Eukaryota; ribozomální DNA; skleníkový efekt; sekvenční analýza DNA; počet mikrobiálních kolonií; shluková analýza; Europe; Greenhouse Effect; sladká voda; Chlorophyll A; Fresh Water; Evropa; chlorofyl; DNA, Bacterial; DNA bakterií; mikrobiologie vody; Altitude; Carbon; ekosystém; RNA ribozomální 16S; In Situ Hybridization, Fluorescence; DNA, Ribosomal; RNA ribozomální 18S; Genetic Variation; Water Microbiology; Phosphorus